2021
DOI: 10.1101/2021.12.22.21268168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association study of Alzheimer’s disease brain imaging biomarkers and neuropsychological phenotypes in the EMIF-AD Multimodal Biomarker Discovery dataset

Abstract: Alzheimer's disease (AD) is the most frequent neurodegenerative disease with an increasing prevalence in industrialized, ageing populations. AD susceptibility has an established genetic basis which has been the focus of a large number of genome-wide association studies (GWAS) published over the last decade. Most of these GWAS used dichotomized clinical diagnostic status, i.e. case vs. control classification, as outcome phenotypes, without the use of biomarkers. An alternative and potentially more powerful stud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Christopher et al also conducted an XWAS and found that the SNP rs11094635 located upstream of the MTM1 gene is associated with beta-amyloid accumulation in the ADNI database (Christopher et al, 2018), but ignored the studies of other QBs in the ADNI database. Note that so far, we are not aware of any XWAS for different types of QBs in the ADNI database, although there have been some previous GWAS based on autosomal loci (Li et al, 2017;Kong et al, 2018;Zhou et al, 2018;Wang et al, 2021;Homann et al, 2022;Oatman 10.3389/fnagi.2023.1277731 Frontiers in Aging Neuroscience 03 frontiersin.org et al, 2023). Therefore, there is an urgent need to perform XWAS on the QBs of the ADNI.…”
Section: Introductionmentioning
confidence: 99%
“…Christopher et al also conducted an XWAS and found that the SNP rs11094635 located upstream of the MTM1 gene is associated with beta-amyloid accumulation in the ADNI database (Christopher et al, 2018), but ignored the studies of other QBs in the ADNI database. Note that so far, we are not aware of any XWAS for different types of QBs in the ADNI database, although there have been some previous GWAS based on autosomal loci (Li et al, 2017;Kong et al, 2018;Zhou et al, 2018;Wang et al, 2021;Homann et al, 2022;Oatman 10.3389/fnagi.2023.1277731 Frontiers in Aging Neuroscience 03 frontiersin.org et al, 2023). Therefore, there is an urgent need to perform XWAS on the QBs of the ADNI.…”
Section: Introductionmentioning
confidence: 99%
“…A small fraction of individuals, approximately 1-5% between the ages of 30 and 60, with Alzheimer's disease develop an early-onset form of the disease. These early-onset forms are often attributed to rare mutations in three genes encoding APP and presenilin 1 and 2 (PSEN1/PSEN2) [148,149]. On the environmental front, modifiable risk factors for AD include hypertension, smoking, diabetes, depression, head injury, physical inactivity, depression, low educational attainment, and obesity [150].…”
Section: Ad Etiologymentioning
confidence: 99%
“…Recent studies have focused on AD endophenotypes, including Aβ and neurodegeneration markers. This approach related to endophenotypes may help identify additional AD-related genetic variants (Potkin et al, 2009;Ramanan et al, 2015;Maxwell et al, 2018;Elsheikh et al, 2020;Homann et al, 2022).…”
Section: Introductionmentioning
confidence: 99%